Exploring the construct validity of tests used to assess L2 productive vocabulary knowledge. (August 2022) - Edmonds, Amanda; Clenton, Jon; Elmetaher, Hosam
Abstract: Vocabulary knowledge in a second language (L2) is thought to be a complex construct and, accordingly, there exist numerous ways to evaluate a L2 learner's vocabulary knowledge. These assessments are generally billed as tests of vocabulary size (i.e., number of words known) or depth (i.e., how well words are known) of either receptive or productive vocabulary knowledge. However, inconsistencies persist in how existing assessments are characterized, leading to sometimes contradictory claims over what these tests are measuring. This state of affairs leads to concerns with the construct validity of the tests in question. In the current study, we contribute to these ongoing discussions with a focus on tests that target productive vocabulary knowledge in L2 English. Four vocabulary tests (three productive, one receptive) were administered to a group of Francophone learners of English, and results were analyzed using an exploratory factor analysis. This analytic approach led to the identification of two underlying constructs, which we labeled receptive vocabulary knowledge and productive vocabulary knowledge, respectively. These results highlight the importance of the crucial distinction between receptive and productive knowledge in the conceptualization of the overall construct of vocabulary knowledge.